Propaganda and Rhetoric in Democracy : History, Theory, Analysis - Henderson, Gae Lyn; Braun, M. J. (Mary Jean) (Book collections on Project MUSE., 2016)
"Offers new perspectives on the history of propaganda, explores how it has evolved during the twentieth and twenty-first centuries, and advances a nuanced understanding of what it means to call discourse propaganda"--